Antimicrobial properties of silver nanoparticles against biofilm formation by Pseudomonas aeruginosa on archaeological textiles - Pietrzak, Katarzyna (2017)
The aims of this work were to: (i) microscopically analyse the pre- and post-Columbian archaeological textiles using Scanning Electron Microscopy with Energy Dispersive X-Ray Analysis (SEM-EDX); (ii) microbiologically analyse the archaeological textiles (from the Southern Andean Area, La Plata Museum); (iii) determine the ability of Pseudomonas sp. isolates from archaeological textiles to biofilm formation by SEM; (iv) assess the anti-biofilm properties of AgNPs protecting cotton against Pseudomonas sp. Results showed the presence of bacteria with proteolytic and lipolytic activities on archaeological textiles, including Clostridium sp. and Pseudomonas aeruginosa. Two nucleotide sequences of 16S ribosomal RNA gene of P. aeruginosa strains were deposited in GeneBank NCBI database with accession numbers: KP842564 (strain 1) and KP842565 (strain 2). Those strains exhibited different morphological and growth characteristics: strain 1 with ability to form biofilms on archaeological textiles was rod-shaped, produced bluish-green pigment, and smaller than strain 2; and strain 2 was pleomorphic and produced brown pigment. The use of silver nanoparticles (90 ppm, φ 10–80 nm) allowed to protecting textiles against P. aeruginosa growth by 63%–97%, depending on the strain and exposition time.